Stability of Hybrid SDEs Driven by fBm - Pei, Wenyi; Zhang, Zhenzhong (Frontiers in Physics, 2021)
In this paper, the exponential stability of stochastic differential equations driven by multiplicative fractional Brownian motion (fBm) with Markovian switching is investigated. The quasi-linear cases with the Hurst parameter H(1/2,1) and linear cases with H(0,1/2) and H(1/2,1) are all studied in this work. An example is presented as a demonstration.